Pharmacokinetic and pharmacodynamic study of triptolide-loaded liposome hydrogel patch under microneedles on rats with collagen-induced arthritis - Gui Chen; Baohua Hao; Dahong Ju; Meijie Liu; Hongyan Zhao; Zhongping Du; Jizi Xia (Acta Pharmaceutica Sinica B, 2015)
Triptolide (TP), a major active component of Tripterygium wilfordii Hook.F. (TWHF), is used to treat rheumatoid arthritis (RA). However, it has a narrow therapeutic window due to its serious toxicities. To increase the therapeutic index, a new triptolide-loaded transdermal delivery system, named triptolide-loaded liposome hydrogel patch (TP-LHP), has been developed. In this paper, we used a micro-needle array to deliver TP-LHP to promote transdermal absorption and evaluated this treatment on the pharmacokinetics and pharmacodynamics of TP-LHP in a rat model of collagen-induced arthritis (CIA). The pharmacokinetic results showed that transdermal delivery of microneedle TP-LHP yielded plasma drug levels which fit a one-compartment open model. The relationship equation between plasma concentration and time was C=303.59×(e−0.064t−e−0.287t). The results of pharmacodynamic study demonstrated that TP-LHP treatment mitigated the degree of joint swelling and suppressed the expressions of fetal liver kinase-1, fetal liver tyrosine kinase-4 and hypoxia-inducible factor-1α in synovium. Other indicators were also reduced by TP-LHP, including hyperfunction of immune, interleukin-1β and interleukin-6 levels in serum. The therapeutic mechanism of TP-LHP might be regulation of the balance between Th1 and Th2, as well as inhibition of the expression and biological effects of vascular endothelial growth factor.